Assessing the Impact of a Collaborative Training Program for Sociology and Social Service Specialists on Their Knowledge, Skills, and Attitudes towards Community Development in Hafr Al-Batin: A Cross-Sectional Survey Study - Sultan Nada S Alharbi; Naif Sanhat N Almutairi; Mashal Ateeah S Aldhafeeri; Taleb Mashnef Aldhafeeri; Mubarak Mashnef Aldhafeeri; Nawor Duhaim Ayadh Al Rashidi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Community development is a crucial aspect of social work and sociology, requiring professionals to possess the necessary knowledge, skills, and attitudes. This study aims to assess the impact of a collaborative training program for sociology and social service specialists on their knowledge, skills, and attitudes towards community development in Hafr Al-Batin, Saudi Arabia. A cross-sectional survey design was employed, with a sample of 120 specialists who participated in the training program. Data were collected using a self-administered questionnaire and analyzed using descriptive and inferential statistics. The findings revealed significant improvements in participants' knowledge, skills, and attitudes following the training program. The study highlights the importance of collaborative training initiatives in enhancing the competencies of social work and sociology professionals, ultimately contributing to effective community development practices. Recommendations for future research and practice are discussed.